The Impact of Urban Concentration on Economic Growth: An Empirical Investigation for a Sample of Countries - Al-Jebouri, Maha; Oran, Ahmad F.; Al-Assaf, Ghazi (International Journal of Economics and Financial Issues, 2020)
Researchers have recently shown widespread interest in the urban concentrations and the resulting economic impacts on global cities. Opinions differ among researchers as some believe in the existence of such effect while the others do not. The study investigates the impact of urban concentration on economic growth by using panel data for 16 countries during 1970-2014. In order to verify the strength of the results, this paper uses two measures for urban concentration, namely urban primacy and urban density. Results show that urban concentration has a positive impact on economic growth and no evidence was found that support the non-linear effect of urban concentration on economic growth. This finding supports many previous empirical studies that highlight the importance of agglomeration economies on economic growth. Keywords: Urban concentration, externalities, urban primacy, urban density, economic growth JEL Classifications: O4, R11, R12 DOI: https://doi.org/10.32479/ijefi.10012